(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background & objective: Alcohol is one of the commonest used intoxicants, being legally and easily available in almost every region of India, leaving aside few states which have banned the sale and use of alcohol. Present study was conducted to find out the correlation between clinical findings, opinion and BAC. Method: Present cross section study was conducted among cases of drunkenness, retrospectively for period of three year at P.D.U. government hospital, rajkot. Result: observation show that all cases were of male and female with predominant age group being between the range of 31-40 years. Maximum cases were occurred at night time and in the month of march. Maximum cases had BAC between 0.05 – 0.08 gm%. Conclusion: there were high degree of variation seen between BAC and clinical findings and clinical opinion due to biological and psychological variation in different individuals.